Comparison of Low and High Dose Cosyntropin Stimulation Tests in the Diagnosis of Adrenal Insufficiency in Septic Shock Patients - Moraes, R. B.; Friedman, G.; Tonietto, T.; Saltz, H.; Czepielewski, M. (Hormone and Metabolic Research, 2012)
Stress situations such as septic shock are accompanied by activation of the HPA axis. Some patients do not activate this axis in stress situations. This blunted response is currently designated as critical illness-related corticosteroid insufficiency (CIRCI). Currently the 250 μg cosyntropin stimulation test is the preferred diagnostic test for CIRCI. Few papers explored the role of the 1 μg cosyntropin test in septic shock patients. In this study, we compared both tests in septic shock patients taking a special interest in the population with intermediary baseline cortisol. Prospective noninterventional study included 74 septic shock patients. After measurement of baseline cortisol all patients received 1 μg of cosyntropin i. v. and 4 h later 249 μg of cosyntropin. We compared the cortisol increase after each test and its relation to mortality and vasopressor therapy. There was a moderate correlation in response to low and high dose cosyntropin, rs=0.55. This correlation in patients with baseline cortisol between 10–34 μg/dl is, rs=0.67. The increase induced by both tests was equally accurate to identify mortality and time of vasopressor withdrawal. Low and high dose cosyntropin tests presented a moderate correlation in patients with baseline cortisol between 10–34 μg/dl. Both tests are equally accurate to identify mortality and time of vasopressor therapy. These results suggest that both tests could be used to diagnose CIRCI.
Keywords: adrenal insufficiency; septic shock; cosyntropin